Innovative Behavior and Creativity: Its Influence on Millennial Employees Performance: Case Study of the Tourism and Hospitality Industry in Bandar Lampung City - Sinta Anzani; Ribhan Ribhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to ascertain how innovatice behavior and creativity affect the productivity of millennial workers in Bandar Lampung's tourist and hospitality sector. In order to accomplish this, a quantitative technique was used in the research, and data was gathered via a Likert scale questionnaire. Because the exact number of population members is unclear, the study used a purposive sampling method to establish the sample size, which amounted to 150 respondents. Software called SPSS 26 was used to examine research data, instruments, and hypothesis testing. This study employed multiple linear regression analysis as its analysis approach. The study's findings demonstrate that innovative and creative behavior benefit millennial workers' performance in the tourism and hospitality sectors in Bandar Lampung. Workers show efficacy in putting ideas into practice, but they are not as proactive in seeking out novel chances. Despite a propensity to be cautious when attempting new ideas, employee innovation has proved to be crucial to organizational success. As a result, encouraging innovation is crucial for raising employee performance and fostering organizational expansion.